Infection control practices and challenges in Pakistan during the COVID-19 pandemic: a multicentre cross-sectional study. Issue 5 (September 2021) - Abbas, Salma; Sultan, Faisal
Background: Patient and staff safety at healthcare facilities during outbreaks hinges on a prompt infection prevention and control response. Physicians leading these programmes have encountered numerous obstacles during the pandemic. Aim/objective: The aim of this study was to evaluate infection prevention and control practices and explore the challenges in Pakistan during the coronavirus disease 2019 pandemic. Methods: We conducted a cross-sectional study and administered a survey to physicians leading infection prevention and control programmes at 18 hospitals in Pakistan. Results: All participants implemented universal masking, limited the intake of patients and designated separate triage areas, wards and intensive care units for coronavirus disease 2019 patients at their hospitals. Eleven (61%) physicians reported personal protective equipment shortages. Staff at three (17%) hospitals worked without the appropriate personal protective equipment due to limited supplies. All participants felt overworked and 17 (94%) reported stress. Physicians identified the lack of negative pressure rooms, fear and anxiety among hospital staff, rapidly evolving guidelines, personal protective equipment shortages and opposition from hospital staff regarding the choice of recommended personal protective equipment as major challenges during the pandemic. Discussion: The results of this study highlight the challenges faced by physicians leading infection prevention and control programmes in Pakistan. It is essential to support infection prevention and control personnel and bridge the identified gaps to ensure patient and staff safety at healthcare facilities.